Prevalence of varicose veins among fast food workers in Cheras, Selangor: A cross-sectional study - Phuah, Ropheca Su Hui (2022)
Background and Objective: Varicose veins (VVs) is a chronic venous disease which commonly develops in lower extremities. Varicose veins are irregular, tortuous and dilated veins of the superficial venous system due to the pooling of blood. Varicose veins can be caused by several risk factors such as age, obesity, heavy lifting, pregnancy, and long-standing hours. Although varicose vein is classified as a work-related disease due to prolonged standing, there are still limitations on epidemiological studies on working populations. Therefore, the objective of the present study is to determine the prevalence of varicose veins and identify the associated risk factors among fast food workers in Cheras, Selangor. Methods: The sampling method used in this study was convenience sampling and the sample size was calculated to be at 210 fast food workers. A descriptive cross-sectional study was conducted among fast food workers in Cheras, Selangor. A self-modified validated questionnaire using Google Forms will be distributed to the fast-food workers via QR scan or social medias. The data collected will be analysed using SPSS 26.0. Significance level will be set at p<0.05 while confidence level set at 95%. Chi-square test (x2) or Fisher’s exact test was used to find the association between the outcome and any categorical variable. Univariate descriptive analysis was used to find the association between the outcome and years of working experiences. Results: Total participants were 210 fast food workers and all responses are being processed. The fast food workers consist of 120 (57.1%) males and 90 (42.9%) females. Out of 201 participants, a minority of 9 participants has diagnosed with varicose veins, representing 4.5% of the prevalence of varicose veins. Varicose veins is significantly associated with social status (p = 0.03), hypertension (p = 0.03), constipation (p = 0.01), diabetes mellitus (p = 0.00), and rheumatoid arthritis (p = 0.06). Conclusion: Varicose veins among fast food workers in Cheras area had a low prevalence of varicose veins. This study has proven that there is a significant association between varicose veins and social status, hypertension, constipation, diabetes mellitus, and rheumatoid arthritis. However, awareness of varicose veins among fast food workers is significant to prevent signs and symptoms and its management.